2011
DOI: 10.1007/s11199-011-0029-y
|View full text |Cite
|
Sign up to set email alerts
|

Experienced and Expected Similarity to Same-Gender Peers: Moving Toward a Comprehensive Model of Gender Segregation

Abstract: Gender segregation is often explained by children being interested in interacting with other children who behave similarly to themselves. Children's beliefs about girls and boys (i.e., their gender cognitions) may also play a role in gender segregation, but this idea has received little attention. In this study, we proposed a model of gender segregation that included similarity on gender-typed behavioral qualities (e.g., rough and tumble play) and gender cognitions concerning perceived similarity to same-gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 52 publications
(73 reference statements)
3
46
0
Order By: Relevance
“…Consistent with these theoretical predictions, previous research has found relations between self-perceived gender typicality and various gender-typed characteristics, including activity preferences, personality traits, and peer preferences (e.g., Egan & Perry, 2001;Martin et al, 2011). Several extant studies have found relations between gender typicality and gender-typed behaviors or characteristics, but there is some disagreement regarding the aspects of gender-typed attributes that are most relevant.…”
Section: Self-perceived Gender Typicality and Gender-typed Attributesmentioning
confidence: 76%
See 2 more Smart Citations
“…Consistent with these theoretical predictions, previous research has found relations between self-perceived gender typicality and various gender-typed characteristics, including activity preferences, personality traits, and peer preferences (e.g., Egan & Perry, 2001;Martin et al, 2011). Several extant studies have found relations between gender typicality and gender-typed behaviors or characteristics, but there is some disagreement regarding the aspects of gender-typed attributes that are most relevant.…”
Section: Self-perceived Gender Typicality and Gender-typed Attributesmentioning
confidence: 76%
“…Work by Perry and colleagues indicated that low self-perceived gender typicality was particularly detrimental when low typicality occurred in conjunction with strong pressure to conform to gender norms (Carver et al, 2003;Egan & Perry, 2001;Yunger et al, 2004). Self-perceived gender typicality has also been linked to various aspects of peer interactions, such as preschool-aged children's peer choices (Martin, Fabes, Hanish, Leonard, & Dinella, 2011) and peer acceptance in childhood and adolescence (Drury, Bukowski, Saldarriaga, & Santo, 2009;Smith & Leaper, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps perceived (i.e., experienced) similarity in school behavior would be a better predictor (cf. Martin et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most fundamental decisions in selecting play partners is whether to play with boys or girls, and most often children prefer same‐gender peers (Martin, ; Martin, Fabes, Hanish, Leonard, & Dinella, ). Children typically spend significantly more time with same‐gender than with other‐gender or mixed‐gender peers (groups that include at least one boy and one girl; e.g., Fabes et al., ; Martin & Fabes, ).…”
Section: Introductionmentioning
confidence: 99%